Weakening of the weekend ozone effect over California's South Coast Air Basin. Issue 21 (2nd November 2015) - Baidar, S.; Hardesty, R. M.; Kim, S.‐W.; Langford, A. O.; Oetjen, H.; Senff, C. J.; Trainer, M.; Volkamer, R.
Abstract: We have observed lower nitrogen dioxide (NO2 ) and ozone (O3 ) during a hot weekend (summer 2010) from aircraft over the entire South Coast Air Basin (SoCAB). Surface concentrations of NO2, O3, and temperature from 1996 to 2014 corroborate that this lower O3 on weekends is increasingly likely in recent years. While higher surface O3 on the weekends (weekend ozone effect, WO3E) remains widespread, the spatial extent and the trend in the probability of WO3E occurrences ( P WO3E ) have decreased significantly compared to a decade ago. This decrease is mostly the result of lower O3 on hot weekends in recent years. P WO3E is lowest in the eastern SoCAB. The major decrease happened during the 2008 economic recession, after which P WO3E has stabilized at a 15–25% lower level throughout most of the basin. Future NO x reductions are likely to be increasingly effective at reducing O3 pollution initially under hot conditions in the coming decade. Key Points: The probability and area in the SoCAB affected by higher weekend O3 have decreased The recent economic recession expedited this decrease Future NO x regulations will be increasingly effective at reducing O3 on hot weekends